Structural Model of Drug Use among Students: The Role of Spirituality, Social Modeling and Attitude to Drugs - samira yavari; robabe nuri; hamid reza hasan Abadi (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study was an attempt to explore the structural relationship between religious activity, religious struggle, attitude to drugs, social modeling, spiritual well-being, and cigarette and tobacco smoking among students. Method: For this purpose, 504 male and female students from Kharazmi University, Agricultural Paradise, and Azad University of Karaj were selected by cluster sampling and they were asked to complete spiritual well-being scale, religious activity scale, religious struggle scale, social modeling scale, negative beliefs about drugs, and the tobacco section of the high-risk behavior questionnaire. Results: The results showed that the effect of religious activity on cigarette and tobacco smoking was mediated by negative beliefs about drugs, social modeling, spiritual well-being, and incentives for drug use. Similarly, the effect of religious struggle on cigarette and tobacco smoking was mediated by spiritual well-being. Conclusion: It seems that religion prevents people joining the unhealthy peer groups by the establishment of moral discipline, internal and external rules, and healthy coping styles therefore, people get less attracted to cigarette and tobacco smoking. Accordingly, these factors should be paid more attention in prevention programs for drug use, particularly cigarette and tobacco that are considered as the gateway to other drugs.